The Use of Information Technologies for the Development of Foreign Language Speech of Students (Eurasian Scientific Herald, 2022)
The article discusses the use of modern information and communication technologies in the teaching of language disciplines at the university. Information competence, which has become one of the main indicators of quality education, is one of the main conditions of modern education, and its formation directly depends on the active activity of students in an open information and educational environment